Comparison of intravitreal bevacizumab and ranibizumab used for myopic choroidal neovascularization: A PRISMA-compliant systematic review and meta-analysis of randomized controlled trials. Issue 12 (March 2019) - Hu, Qiuming; Li, Haoyu; Du, Yi; He, Jianfeng
Abstract: Background: To evaluate the effect of intravitreal bevacizumab (IVB) and ranibizumab (IVR) for the treatment of choroidal neovascularization (CNV) secondary to pathologic myopia (PM) by meta-analysis. Methods: Pertinent publications of randomized controlled trials (RCTs) were identified through systemic searches of PubMed, EMBASE, Web of science, Cochrane Library, clinicaltrials.gov, CNKI, CQVIP, and Wanfang database. All comparative studies of IVB or IVR as treatment for CNV secondary to pathologic myopia were included. Meta-analysis of these RCTs was performed using Review Manager 5.3 software. The χ 2 test and I 2 values were used to analyze heterogeneity. Measurements included best-corrected visual acuity (BCVA) and central foveal thickness (CFT). Results: A total of 3 randomized controlled clinical trials involving 158 eyes were included, 81 eyes in IVB group and 77 eyes in IVR group. Compared with baseline, at 1, 3, 6, and 12 months after IVB or IVR treatment, BCVA was significantly increased. Change of BCVA at 1, 3, 6, and 12 months did not vary significantly between IVB and IVR group (1 month: Z = 0.30, 95% CI = −0.08 to 0.11, P = .76; 3 months: Z = 0.36, 95% CI = −0.10 to 0.15, P = .72; 6 months: Z = 0.17, 95% CI = −0.10 to 0.12, P = .86; 12 months: Z = 0.64, 95% CI = −0.15 to 0.08, P = .52). Conclusion: Both IVR and IVB can significantly improve BCVA of eyes with mCNV, but there was no significant difference between the 2 therapies on the treatment of mCNV.